2021
DOI: 10.3390/su13105418
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Trade during COVID-19 Pandemic: Establishing a Conceptual Model Including COVID-19 Impact

Abstract: The conceptual research aims to identify antecedents conducive to bilateral trade during the COVID-19 pandemic. Considering the relevance of bilateral trade for foreign policy and economy studies, there is a need for a renewed framework in times of extreme economic instability. As international commerce is essential for improving the country’s economy, we have examined how economic distance, population, trade percentage of GDP, exchange rate, and political changes interconnect and relate to COVID-19, influenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 115 publications
(109 reference statements)
0
16
0
6
Order By: Relevance
“…The study uncovered that COVID-19 led to underutilization of capital, a decline in manufacturing output, a rise in production costs, and inflation in export-import trade costs. 9 During the pandemic, there has been enormous loss of human life, which has impacted social, economic, and political disruptions. The COVID-19 pandemic has severely impacted economies, and the study revealed that there is a negative association between the COVID-19 pandemic and trade.…”
Section: Trade Costmentioning
confidence: 99%
“…The study uncovered that COVID-19 led to underutilization of capital, a decline in manufacturing output, a rise in production costs, and inflation in export-import trade costs. 9 During the pandemic, there has been enormous loss of human life, which has impacted social, economic, and political disruptions. The COVID-19 pandemic has severely impacted economies, and the study revealed that there is a negative association between the COVID-19 pandemic and trade.…”
Section: Trade Costmentioning
confidence: 99%
“…gained by questionnaire surveys and interviews (Shakil and Munim, 2020;Saif and Ruan, 2021). Other studies have also quantitatively identified the key factors affecting the survival of small business after the first wave of COVID-19 (Katare and Marshall, 2021).…”
Section: Open Access Edited Bymentioning
confidence: 99%
“…Hence, this study largely concentrated on literature published recently on the impact of Covid-19 on international trade. Saif et al (2021) introduced a conceptual model in capturing the impact of Covid-19, arguing that the existing theoretical models in the field of international trade lacked capacities to capture the effect arising from a global-level pandemic such as Covid-19. The authors emphasised three main channels through which Covid-19 affects the international trade flows in the short to medium run; namely financial, technological, and policy shocks.…”
Section: Literature Reviewmentioning
confidence: 99%